Anticancer, antioxidant and antimicrobial activities of Suaeda fruticosa related to its phytochemical screening - Samiullah; Asghari Bano; Sisay Girmay; Ghee Tan (International Journal of Phytomedicine, 2012)
Concerning anticancer evaluation of methanolic extract of Suaeda fruticosa arial parts demonstrated the utmost anticancer activity with IC50 value of 50 μg/ml against human lung carcinoma (LU-1), the same extract displayed a preeminent activity with IC50 ≥ 50 μg/ml against hormone dependent prostrate carcinoma (LnCaP). The analyzed root extract exhibited IC50 ≤ 65 μg/ml against hormone dependent prostrate carcinoma (LnCaP) whereas, the same extract demonstrated IC50 ≤ 55 μg/ml against human lung carcinoma (LU-1). The highest content of total phenolic (0.52-0.67 mg gallic acid equiv./g) and total flavonoids (0.44 mg/g D/W) content was detected in the arial part of Suaeda fruticosa. MIC value of 50-85 μg ml−1 has been observed gainst Aspergillus fumigates, Aspergillus niger, Fusarium solani and Mucor sp in comparision with 1-2.5μg/ml of Terbinafine used as a standard fungicide. MIC value of 80 μg/ml and 35 μg ml−1 of Suaeda fruticosa arial parts and root extract against bacterial pathogen Klebsiella pneumonia and 50 and 90 μg ml−1 against Enterococcus has been measured. DPPH radical scavenging activity of Suaeda fruticosa with IC50 values of ≤ 100 μg/ml and ≤ 50 μg ml−1 was observed whereas, hydrogen peroxide scavenging activity with IC50 values of ≤ 12.5 μg/ml for arial parts and ≤ 25 μg ml−1 for the root extract of Suaeda fruticosa has been shown with galllic acid (R2= 0.819) and ascorbic acid (R2= 0.728). These data suggested that the methanolic extract of Suaeda fruticosa could be potential candidates for natural antioxidants and anticancer. The findings demonstrated the remarkable potentiality of Suaeda fruticosa as valuable source of antioxidant and anticancer capacities.